1992
DOI: 10.3354/meps083241
|View full text |Cite
|
Sign up to set email alerts
|

Pigment composition, spectral characterization and photosynthetic parameters in Chryso-chromulma polylepis

Abstract: The photobiological response of an isolate of the prymnesiophyte Chrysochromulina polylepis, obtained from a bloom in the Skagerrak in May-June 1988, was evaluated with respect to pigment composition, spectral dependence of light harvesting, and photosynthetic parameters of cultures grown at 75 to 120 gm01 m-2 S-' irradiance, 16 h day length and 15°C. Results were compared to similarly grown cultures of the diatom Skeletonerna costatum that appeared before and after the C. polylepis bloom. Chl a-specific absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
(31 reference statements)
2
33
1
1
Order By: Relevance
“…Nevertheless, there is still no concrete evidence for this hypothesis. In fact, at least 2 research groups (Haxo 1985, Johnsen et al 1992, Johnsen & Sakshaug 1993) have shown a light-harvesting function for 19'-hexanoyloxyfucoxanthin. Recently, Stolte et al (2000) have proposed that the pathway of synthesis of carotenoids in Emiliania huxleyi (a haptophyte) has steps leading from diadinoxanthin to fucoxanthin and from fucoxanthin to 19'-hexanoyloxyfucoxanthin.…”
Section: Photoadaptation and Photoacclimation Of Phytoplankton Populamentioning
confidence: 99%
“…Nevertheless, there is still no concrete evidence for this hypothesis. In fact, at least 2 research groups (Haxo 1985, Johnsen et al 1992, Johnsen & Sakshaug 1993) have shown a light-harvesting function for 19'-hexanoyloxyfucoxanthin. Recently, Stolte et al (2000) have proposed that the pathway of synthesis of carotenoids in Emiliania huxleyi (a haptophyte) has steps leading from diadinoxanthin to fucoxanthin and from fucoxanthin to 19'-hexanoyloxyfucoxanthin.…”
Section: Photoadaptation and Photoacclimation Of Phytoplankton Populamentioning
confidence: 99%
“…Chl c represents a mixture of slightly spectrally distinct components: chl c,, chl C?, chl c3 and magnesium 2,4-divinyl phaeoporphyrin a, monomethyl ester (Mg-D). These have in vivo absorption maxima at approximately 460 to 470, 586 and 635 nm (Rowan 1989, Bidigare et al 1990a, Johnsen et al 1992, Johnsen & Sakshaug 1993.…”
Section: Introductionmentioning
confidence: 99%
“…The major light-harvesting carotenoids, i.e. the fucoxanthins and the 19'-acyloxyfucoxanthins together with pendinin and prasinoxanthin absorb in vivo mainly at 450 to 550 nm (Prezelin & Boczar 1986, Bidigare et al 1987, 1990b, Sathyendranath et al 1987, Johnsen et al 1992). Phycobiliprotein-dominated pigment systems of many cyanobacteria and cryptophytes absorb green to orange light (480 to 600 nm) efficiently (Prezelin & Boczar 1986, Bidigare et al 1987.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations